Optimizing Cultural Events for Destination Branding and Community Empowerment in Tenganan Dauh Tukad - Swandewi, Ni Kadek; Winatha, Mahendra Adi; Sukariyanto, I Gede Made; Rahjasa, Putu Surya Laksana; Rastitiati, Ni Kade Juli (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
This community service project aims to empower the local community of Tenganan Dauh Tukad by enhancing their capacity to promote cultural tourism through digital platforms. Framed around the theme of Tenganan as The Living Culture Destination, the project was implemented in three phases: documentation, content development, and community training. In the first phase, local youth were involved in capturing high-quality photo and video content during the traditional Perang Pisang event. In the second phase, the materials were edited into Instagram-optimized formats using a custom visual identity that reflects the village’s values—Asli (Authentic), Sakral (Sacred), Teguh Tradisi (Tradition-bound), Edukatif (Educational), and Elegan (Elegant). The third phase focused on training participants in managing Instagram, creating content calendars, and applying preset filters through the Lightroom mobile app. The outcome includes the rebranding of the village’s Instagram account to @tengananexperience and the development of a content strategy based on the pillars: Be Promotional, Be Human, and Be Entertaining. This initiative not only improved the digital skills of the community but also strengthened their cultural pride and established a sustainable model for cultural tourism promotion. Keywords: community service, digital empowerment, cultural tourism, Instagram branding, Tenganan Dauh Tukad, sustainable tourism.